Study on Fish Species Diversity of Mahendranath pond Siwan Bihar - Manoj Kumar Pandey, Dr (International Journal of Pharmaceutical & Biological Archive, 2012)
Study on Fish Species Diversity of Mahendranath pond Siwan Bihar